ANALISIS PEMOTONGAN,PELAPORAN, DAN PENYETORAN PAJAK PENGHASILAN PASAL 21 PEGAWAI TETAP TAHUN 2020 (STUDI KASUS BANK BTPN KC BANJARMASIN) - Jemmy Perdana; Saipudin (Universitas Lambung Mangkurat, 2021)
Destination. This study aims to find out how to analyze the withholding, deposit, and reporting of income tax article 21 for permanent employees at the national pension savings bank. The data analysis technique used in this research is descriptive technique, with this the researcher can describe the research object under study using qualitative methods. The results obtained from the study indicate that withholding, depositing, and reporting income tax article 21 at Bank BTPN KC Banjarmasin is in accordance with the provisions of Law NO/36/2008 Income Tax